Pengaruh Strategi Diversifikasi, Leverage, Earning Growth, dan Ukuran Perusahaan terhadap Kinerja Perusahaan Perbankan - Azzahra, Retno; Fauzan (Jurnal EMT KITA, 2024)
The purpose of this study was to analyze the effect of diversification strategy, leverage, earning growth, and company size on the performance of banking companies. The type of research used is quantitative. The methods used in this research are descriptive and verification methods. The data used in this research is secondary data. The population in this study were banking companies or banks listed on the Indonesia Stock Exchange. The sample or sampling technique used in this study was purposive sampling. The number of samples in this study were 30 banks listed on the Indonesia Stock Exchange. Data collection techniques by studying, understanding, reviewing journals, books and other sources. The data analysis technique uses multiple linear regression techniques, classical assumption tests which include normality, multicollinearity, heteroscedasticity, and autocorrelation tests, F tests, t tests, and R² tests. The results of this study are Diversification Strategy has a significant influence on Company Performance. Leverage has a significant effect on Company Performance. Earning Growth has no significant effect on Company Performance. Company Size has no significant effect on Company Performance. Simultaneously, Diversification Strategy,Leverage, Earning Growth, and Company Size have a significant influence on Company Performance.